Analysis of Determinants Influencing The Labor Force Participation Rate (LFPR) of Women in East Java Province For The Years 2018-2022 - Cholifah, Nurul; Sutrisno, Sutrisno (Gorontalo State University, 2024)
The role of women is not only to be a wife and housewife, but their existence can provide its color in economic activities. This research aims to analyze of determinants influencing the labor force participation rate of women in East Java Province for the years 2018-2022. This research consisted of 38 regencies/cities in East Java Province over 5 years so there were 190 observations, obtained from the Central Statistics Agency (BPS). This research method uses quantitative analysis with panel data regression. The research results show that the best model is the Fixed Effect Model. Partially, women's per capita expenditure (X1) has a positive and insignificant effect on the labor force participation rate of women (Y). The average number of years of schooling for women (X2) has a positive and significant effect on the labor force participation rate of women (Y). The minimum wage in districts/cities (X3) has a negative and insignificant effect on the labor force participation rate of women (Y). Gross Regional Domestic Product (X4) has a negative and significant effect on the labor force participation rate of women (Y). Simultaneous research results in women's per capita expenditure (X1), average years of schooling for women (X2), minimum wage in districts/cities (X3), and Gross Regional Domestic Product (X4) together have a significant effect on the labor force participation rate of women (Y). As the number of labor force participation rate of women increases every year, it is hoped that the development strategy in East Java District/City will move towards a strategy that prioritizes improving the quality of human resources, through soft skills and hard skills training.